Indole-linked triazine-dibenzothiophene/dibenzofuran based host materials for high-efficiency green and red phosphorescent organic light-emitting diodes. (February 2020) - Wang, Huan; Zhang, Yiyao; Song, Wenxuan; Huang, Jinhai; Xia, Zhenyuan; Su, Jianhua
Abstract: Two host heterocyclic compounds 5-(dibenzo[b, d]furan-4-yl)-1-(4, 6-diphenyl-1, 3, 5-triazin-2-yl)-1H-indole (FITRZ ) and 5-(dibenzo[b, d]thiophen-4-yl)-1-(4, 6-diphenyl-1, 3, 5-triazin-2-yl)-1H-indole (TITRZ ) were synthesized by CN coupling reaction of triazine and dibenzothiophene/dibenzofuran moiety with a 1, 5-bridged indole unit. Their photo-physical, thermal and electrochemical properties were fully explored, and the results indicate that both of them are promising phosphorescent host materials for green and red PhOLED devices with low on-set potentials. For example, the green PHOLED based on TITRZ showed the maximum current and external quantum efficiency up to 85.9 cd/A and 23.7%. Meanwhile, the red PhOLED based on FITRZ yielded the maximum current and external quantum efficiency of 41.3 cd/A and 18.8% with a turn-on voltage of 3.0 V. Graphical abstract: Image 1 Highlights: Noble host materials for green and red PhOLED devices with low on-set potentials. Green PHOLED based on TITRZ with EQE up to 23.7%. Red PhOLED based on FITRZ yielded EQE of 18.8% with a turn-on voltage of 3.0 V.